The Eskimo Drum Dance - Arima, E.Y. (ARCTIC, 1974)
The drum dance which combines the booming beat of a large tambourine drum with poetic song and dance is perhaps the most pleasurable and intense expression of Eskimo culture. This art is particularly refined among the Copper Eskimos around Coronation Gulf. . Drum dancing used to take place mainly in winter, when the Copper Eskimos congregated for breathing-hole sealing, or whenever visitors from afar were met. A large snowhouse used to be made, performance outdoors being tabu, though not today . Decorative festive dress was worn including at times a striped dancing cap surmounted by a loon's beak. Up to about fifty persons might crowd inside, the men forming an inner circle and the rest along the walls. If necessary, the yard-wide drum head of thin dehaired caribou skin is moistened to tighten it to give the desired rumbling resonance. The rim is a thin wood strip two to three inches wide with a handle attached to it. Large and quite heavy, the drum takes strength and practice to be wielded in one hand. Women can lower it for ease. Beating is done on the rim from below with a heavy foot-long stick, the men striking on opposite points of the hoop in alternation while women beat closer to the handle. To begin, the performer sounds a few beats as if testing the instrument, waves it up and down or taps lightly and rapidly on the skin from below. Starting the song, he beats the rim and lets the drum swivel to meet the stick. The audience joins in the singing, commonly led by the performer's spouse, freeing him to concentrate on drumming and dancing and to be transported into an exalted joyous state. With knees slightly bent the dancer moves around the small inner circle, shifting from foot to foot, sometimes hopping lightly. The music is basically in 2/4 time, and the simplest drumming is two equal beats per measure, the tempo ranging from about fifty to eighty measures per minute. A common variation is to beat strongly on the left side of the drum then stop the swing back almost soundlessly on the right. For more ...